MENINGKATKAN KEMAMPUAN GURU DALAM MENGEFEKTIFKAN PEMBELAJARAN MELALUI PROGRAM PEMBINAAN PROFESIONAL GURU DAN SUPERVISI KELAS DI SMKN 1 MAMUJU KABUPATEN MAMUJU - Makhmudi Makhmudi (Universitas Negeri Makassar, 2022)
This research aims to improve teachers' ability to make learning effective through a teacher professional development program and class supervision at SMKN 1 Mamuju in the 2018/2019 academic year. This research is classified as a school action research involving 12 teachers who need to improve their ability to effectively manage their learning. The research was conducted in three cycles and each cycle consisted of four stages: planning, implementing, observing and reflecting. The performance indicators set are when there is an increase in the ability to effectively manage learning through teacher professional development and classroom supervision. From the results of the study it was found that there was an increase in ability to effectively manage learning in cycle I, namely those who obtained an A value of 25%, a B value of 25% and a C value of 50%, in cycle II, which obtained an A value of 50%, a B value of 41, 67% and a C value of 83.3%, while in cycle III which obtained an A value of 66.67%, a B value of 25% and a C value of 83.3%. Thus it can be concluded that through teacher professional development programs and classroom supervision can improve the ability of teachers to make learning effective. Thus it is suggested to the principal that through the teacher professional development program and class supervision can be used as an alternative in increasing the ability of teachers to make learning effective.